2007
DOI: 10.1089/zeb.2007.0505
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Primitive Myelopoiesis in the Zebrafish by Spi-1/Pu.1 and C/ebp1

Abstract: The zebrafish has become a powerful tool for analysis of vertebrate hematopoiesis. Zebrafish, unlike mammals, have a robust primitive myeloid pathway that generates both granulocytes and macrophages. It is not clear how this unique primitive myeloid pathway relates to mammalian definitive hematopoiesis. In this study, we show that the two myeloid subsets can be distinguished using RNA in situ hybridization. Using a morpholino-antisense gene knockdown approach, we have characterized the hematopoietic defects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 47 publications
5
46
1
Order By: Relevance
“…51,54,55 These findings prompted us to speculate that, in zebrafish, Cebp1 and c-Myb may form a genetic network to regulate neutrophil development.…”
Section: Suppression Of C-myb Function In Zebrafish Blocks Neutrophilmentioning
confidence: 99%
“…51,54,55 These findings prompted us to speculate that, in zebrafish, Cebp1 and c-Myb may form a genetic network to regulate neutrophil development.…”
Section: Suppression Of C-myb Function In Zebrafish Blocks Neutrophilmentioning
confidence: 99%
“…pu1 expression is lost in gata5 and gata6 morphants but, although this could explain the absence of myelopoiesis, a role for pu1 in haemangioblast formation or endothelial development has not been established (Rhodes et al, 2005;Su et al, 2007). However, analysis of pu1 morphants showed that pu1 is required only for myeloid development and not at all for the endothelial programme (see Fig.…”
Section: Research Articlementioning
confidence: 99%
“…However we could not preclude the possibility that Ncor2 may function to activate the transcription of spi1b required for primitive myelopoiesis directly by remodeling their chromatin, because such mechanisms have been reported in a few cases for the other co-repressors' function (O'Malley and McKenna, 2008). mfap4 1 macrophages and mpx 1 neutrophils are the mature myeloid cells developing from spi1b 1 myeloid cells (Su et al, 2007;Xu et al, 2012). The regulation mechanism of fate determination of macrophages and neutrophils has been extensively studied.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…mRNAs containing full-length of coding sequences of tal1, lmo2, and spi1b were in vitro transcribed as we reported previously (Liang et al, 2012). The full-length coding sequence of spi1b (Su et al, 2007) was cloned by RT-PCR using primers of ATGCTGCATCCGTACAG (forward) and TTACATGTAATGCTTTC (reverse).…”
Section: Qrt-pcrmentioning
confidence: 99%